Effect of Sudarshan Kriya Yoga on anxiety, depression, and quality of life in people with type 2 diabetes: A pilot study in Kuwait. Issue 3 (May 2019) - Shiju, Rashmi; Thomas, Daisy; Al Arouj, Monira; Sharma, Prem; Tuomilehto, Jaakko; Bennakhi, Abdullah
Abstract: Aim: This pilot study in Kuwait was aimed to assess the effect of Sudarshan kriya yoga (SKY) on anxiety, depression and total quality of life in people with type 2 diabetes mellitus (T2DM). Methods: 26 T2DM patients aged greater than 30, male and female visiting the outpatient clinic of Dasman Diabetes Institute were enrolled for the study. Pre and post 5 day SKY intervention responses of participants on psychosocial problems were evaluated using four questionnaires (Hamilton anxiety, patient health questionnaire (PHQ-9), Hospital anxiety depression and WHO total quality of life (QOL). Biochemical parameters; such as lipid profile, glycated hemoglobin (HbA1c) were measured at baseline and after 15 weeks of SKY practice. Results: The mean age of the participants was 56.7 (±11.4 SD) years, and mean duration of diabetes 15.0 (±9.3 SD) years. Comparison of responses before and after intervention indicated a significant improvement in the QOL, depression, anxiety and insomnia. But no significant improvement in glycemic control. Conclusion: Results indicate that SKY can be potentially beneficial for treating anxiety, insomnia, and depression associated in people with T2DM and in improving the quality of life in people with T2DM.